2021 IEEE 46th Conference on Local Computer Networks (LCN) 2021
DOI: 10.1109/lcn52139.2021.9524932
|View full text |Cite
|
Sign up to set email alerts
|

SecGrid: a Visual System for the Analysis and ML-based Classification of Cyberattack Traffic

Abstract: Due to the increasing number of cyberattacks and respective predictions for the upcoming years with even larger numbers of occurrences, companies are becoming aware not only that the digitization of their businesses is essential, but also that the adoption of efficient cybersecurity strategies is crucial. Therefore, approaches for a better understanding and analysis of cybersecurity are essential.Thus, SecGrid, a Machine Learning (ML) empowered platform for analyzing, classification, and visualization of cyber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…On the other hand, other researchers focused on collecting data concerning specific types of attacks to be collected and classified. The DDoSGrid dashboard was created in [17] to analyze and visualize distributed denial-of-service (DDoS) attacks. This was motivated by the demand for network operators to recognize the characteristics and behaviors of attacks, and hence more effectively plan cybersecurity strategies.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, other researchers focused on collecting data concerning specific types of attacks to be collected and classified. The DDoSGrid dashboard was created in [17] to analyze and visualize distributed denial-of-service (DDoS) attacks. This was motivated by the demand for network operators to recognize the characteristics and behaviors of attacks, and hence more effectively plan cybersecurity strategies.…”
Section: Related Workmentioning
confidence: 99%
“…Our work, in turn, contributes to both works in collecting data from the whole world. Both works proposed in [17,18] focused on collecting data concerning specific types of attacks, i.e., DDoS attacks, to be clustered and classified. Hence, our work contributes to both works in collecting tweets concerning different types of cyberattacks published on the X platform.…”
Section: Comparison With Existing Workmentioning
confidence: 99%
“…Such activities often indicate recurring patterns in network usage and can be malicious or benign. Inferring periodic activities of unknown origins will typically trigger a detailed post-mortem and offline forensic analysis by the network operator [Franco et al 2021] to identify the observed periodic activities' root cause(s). Examples of such efforts include detecting anomaly behavior [Du et al 2018, Ji, Choi e Jeong 2015, reconstructing the signal of a network communication [Jiang et al 2020], and analyzing the energy spectrum [Yue et al 2018].…”
mentioning
confidence: 99%